Identification of equine establishments with different performance status of endurance horses - Faisal, Nurul Hafizah; Mohd Adzahan, Noraniza; Goh, Yong Meng (2012)
A population survey was conducted on seven equine establishments in Peninsular Malaysia, which actively involved in equine endurance sports. This study presents data obtained through questionnaires and interviews of horse personnel. Total number of horses involved in the study was 115 endurance horses of different breed, gender, age and performance level from various equine establishments. Data collected were analyzed using SPSS version 19 (Kruskal Wallis). More than 50 % of horse population from the equine establishments involved was represented by pure Arabians. The pure Arabians were also observed in all performance categories – 40, 80, 120 and 160 km of racing distances. Majority of the endurance horses were geldings and females with the total of 51 % and 36 % respectively. About half of the population was between the age of 6 to 8 years and most of them were found in all performance categories. There were significant relations between breed, gender, age and establishments based on the performance categories in this study. Majority of the equine establishments were involved in the 40 and 80 km racing categories, both representing approximately 30 % of the total population, followed by the 80 km. Both 120 and 160 km racing categories were represented equally by 18 % of the total endurance horse population surveyed.